Beyond age: Decoding the investment DNA of generations Z and Y in Indonesia - Debbi Chyntia Ovami; Henny Zurika Lubis; Esa Setiana; Ita Mustika; Sari Wulandari (Investment Management & Financial Innovations)
Investment decisions are a matter of how individuals should allocate funds into investment forms that provide future benefits. This paper investigates the impact of financial literacy, perceptions of risk and returns, family background, income, and financial technology proficiency on investment decisions among Generations Z and Y in Indonesia. This study uses a quantitative approach, using primary data from 240 respondents through purposive sampling. Primary data were collected through a questionnaire survey to collect respondents’ perceptions and investment decisions. The Likert scale assesses indicators by eliciting responses to statements and questions. The Structural Equation Model Partial Least Square (SEM-PLS) approach was employed for analysis utilizing WarpPLS 8.0 software. The results show that financial literacy, risk and return perception, income, and fintech proficiency significantly influence investment decisions (p < 0.05), while family background does not (p > 0.05). In addition, fintech proficiency mediates the effects of financial literacy, risk perception, family background, and income on investment decisions (p < 0.05). These findings suggest that improving financial literacy and fintech skills can lead to better investment decisions among young investors. This study highlights the need for targeted financial education programs and innovative fintech solutions to support informed investment choices. Further research is recommended to explore additional factors influencing investment decisions and to develop strategies to improve financial decision-making in this demographic group.